Aligning cardiac monitoring with American Heart Association Guidelines: Impact on utilization, hemodynamic monitoring, and outcomes - Brian Hilliard; Tanvi Mehta; James Grace; Deborah L. Pestka; Nicholas E. Ingraham; Timothy Beebe; Christopher Tignanelli; Genevieve B. Melton; Nathan Shippee; Joseph S. Koopmeiners; Michael Usher (PLoS ONE, 2026)
Background Overuse of continuous cardiac monitoring can lead to poor patient experience, increased costs, and decreased efficiency. Because significant variation in continuous cardiac monitoring ordering exists, implementation strategies that promote care in alignment with practice standards and an examination of use cases that fall outside of standards are needed. The purpose of this study, therefore, was to evaluate if implementation of American Heart Association (AHA) practice standards on continuous cardiac monitoring could reduce utilization without jeopardizing patient safety. Methods We conducted a prospective pre-post study including a 2 year prospectively collected baseline against a 10-month post intervention period within a 10-hospital health system. An electronic health record (EHR) order set was implemented to align care with AHA continuous cardiac monitoring practice standards. We compared continuous cardiac monitoring utilization, adherence to standards, as well as clinical outcomes including mortality and length of stay. Finally, we investigated the rate and impact of hemodynamically significant events (hypotension, bradycardia, and tachycardia) before and after the intervention. Results We compared 117,814 hospitalizations pre-implementation against 49,006 post implementation finding significant reductions in total telemetry use, and no significant change in outcomes. Overall, patients with telemetry use outside of standards had higher mortality, longer length of stay, and higher readmission rates. The intervention was associated with a higher rate of hypotensive events which occurred off cardiac monitoring. This was not associated with worse outcomes. Conclusions An EHR tool to align care with continuous cardiac monitoring practice standards safely reduced overall continuous cardiac monitoring utilization. Use outside of practice standards persisted and was primarily focused on monitoring for potential hemodynamic instability. We found no evidence that continuous cardiac monitoring was associated with improved outcomes in unstable patients. Continuous cardiac monitoring for potentially unstable patients can likely be replaced for non-cardiac indications with continuous heart rate monitoring.